The impact of ball recovery type, location of ball recovery and duration of possession on the outcomes of possessions in the English Premier League and the Spanish La Liga - Cooper, D.; Pulling, C. (Science and Medicine in Football, 2020)
Objective: The aim of this study was to explore the impact of the ball recovery type, location of ball recovery and the duration of the possession on the outcomes of possessions in both the EPL and the Spanish La Liga.